Down Memory Lane ... as LAEL Celebrates its Golden Jubilee - Rajagopalan, Kanavillil (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2021)
In this paper, I attempt to trace the evolution of LAEL over the 50 years of its history, intertwining the narrative with my own personal trajectory since my arrival in Brazil in 1976. The narrative makes no claim to being a step by step account of the different facets of the Programme’s history. Rather, the focus is on how its developments through the years mirror the fortunes of the very area of academic pursuit we call Applied Linguistics.